Application of Theory of Constraint Principle for Production Scheduling in PT. Nusira Medan - Parinduri, Luthfi; Arfah, Mahrani; Hasibuan, Abdurrozzaq; Sulaiman, Oris Krianto; Darmawati, D; Asaad, Mhd. (International Journal of Engineering and Technology, 2018)
PT. Nusira Medan as a producer of Crumb Rubber, based on orders with First Come First Serve (FCFS) rules. Limited resources lead to delay in order completion time. This causes delays in delivery of orders to consumers. Therefore, this research is to obtain optimal scheduling sequence with the criteria of minimizing waiting time, idle time and makespan The use of the Theory of Constraints principle is to arrange production scheduling as a solution to the problem. Expected results are the most appropriate scheduling to be applied to the company in accordance with the criteria of waiting time, idle time and makespan. The result of the research is the sequence of job scheduling sequence1-2-3-4-5 resulted in makespan of 26.47 days or 211,76 hours, idle time of 37.25 hours and waiting time of 32.85 hours . While the scheduling systems under the First Come First Serve (FCFS) rules of job scheduling sequence to 1-2-3-4-5 with makepan value of 27.46 days, idle time of 48.84 hours and waiting time of 54.24 hours. The reduction of makespan of 0.98 days or 7.84 hours, idle time reduction of 11.59 hours and waiting time of 21.39 hours